Pengaruh Penekanan Titik Akupresur Taixi (Ki3), Sanyinjiao (Sp6) Terhadap Penurunan Tekanan Darah Pada Lansia Dengan Hipertensi Di PSTW Jember - Sulton Wariin (Jurnal Kesehatan dr. Soebandi, 2018)
Most prevalent diseases in the elderly is of Non-Infectious Diseases, one of which is hypertension. Hypertension is a silent killer which symptoms can various in each others and similar with the symptoms of other diseases. 25.8% hypertension, causes at least 45% of deaths due to heart disease and 51% of deaths due to stroke. The kind of treatment consist of pharmacology and nonpharmacology. One of the non-pharmacology tretment is acupressur therapy The purpose of this study to determine the emphasis effect of acupressure points Taixi (Ki3), Sanyinjiao (SP6) to reduction blood pressure in the elderly with hypertension in PSTW Jember. The study design used is quasy experiment one group pretest posttest. Samples taken by simple random sampling, that is the elderly aged over 60 years with hypertension in Jember PSTW as many as 20 person. After the acupressure therapy mostly elderly blood pressure is decreased. The results were analyzed using SPSS with paired sample t-test if normal data distribution and the Wilcoxon signed rank test if data distribution is not normal. Results of analysis using paired samples t-test showed that the value of systole p = 0.001 (p < α). This research of the value of MAP p= 0.000 (p < α) and diastole using the Wilcoxon signed rank test was obtained p = 0.004 (p < α ) mean that suppression effect of acupressure points Taixi (Ki3) and Sanyinjiao (SP6) effective to decrease blood pressure in the elderly with hypertension in PSTW Jember